Post-war Restoration of the AzPOS Network in Karabakh - Maharramli, Z.S.; Suleymanov, T.I.; Gasimova, A.A.; Ahmadov, Sh.A. (Herald of Azerbaijan Engineering Academy, 2024)
The main purpose of the article is to describe the restoration of geoinformation works carried out on the territory of Karabakh. NAVSTAR satellite systems were used in the restoration work. The value of the base stations established in the liberated areas is very high. N the liberated territories of the Republic of Azerbaijan, 8 permanent reference stations were installed (Fuzuli, Jebrail, Zangilan, Kelbajar1, Kelbajar2, Agdam, Shusha, Lachin). The locations of these reference stations are determined to cover each other within a radius of 30 km. The assigned locations of each station were then checked and 24-hour test measurements were carried out at Fuzuli station using a Leica GS18 GNSS.